Two CTA working documents: [Technical consultation on assessing the performance and impact of agricultural information products and services - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Technical consultation on assessing the performance and impact of agricultural information products and services CTA. 2002. 172 pp., CTA working document 8027. 5 credit points